Self-Help Groups and Their Role in Enhancing Economic Opportunities for Women in Nagpur's Slums (International Journal of Food and Nutritional Sciences, 2023)
This research paper examines the role of Self-Help Groups (SHGs) in enhancing economic opportunities for women residing in the slums of Nagpur. Despite significant socio-economic challenges, SHGs have emerged as vital instruments for women's empowerment, providing access to financial resources, skills training, and a platform for collective bargaining. This study employs a mixed-methods approach, combining quantitative data from surveys of 250 women involved in SHGs and qualitative interviews with key stakeholders, including SHG leaders and local community organizers. The findings reveal that participation in SHGs significantly improves women's economic status by increasing their income, enhancing their employment opportunities, and fostering entrepreneurial skills. Additionally, the study highlights the critical factors contributing to the success of SHGs, such as training programs, support from governmental and non-governmental organizations, and the establishment of strong networks among women. The paper concludes that SHGs not only empower women economically but also play a crucial role in challenging social norms, thereby contributing to broader gender equality in the community. These insights underscore the necessity for policymakers and development practitioners to support and scale up SHG initiatives as a sustainable means of fostering women's economic empowerment in urban slum contexts.